Deutsche Phonetik und Prosodie im DaF/DaZ-Unterricht für italienische Lernende - Missaglia, Federica (Kritik. Rivista di letteratura e critica culturale, 2023)
This paper is concerned with the acquisition of FL/SL German phonetics and prosody by Italian learners. It moves from phonetic and phonological theory and research towards teaching practice. In the theoretical framework of contrastive analysis the paper starts by illustrating differences and similarities between Italian and German phonetics and phonology at the segmental, intersegmental and suprasegmental level. It then accounts for research in the field of FL/SL phonetic acquisition, specifically addressing the case of German as a Foreign Language (‚DaF‘) and German as a Second Language (‚DaZ‘) in Italy. Since empirical evidence shows that most phonetic interferences and negative transfer phenomena depend on prosody (mainly rhythm and prominence), the paper pleads for a ‚prosodic turn‘ in DaF/DaZ education. Referring to a specific teaching method based on contrastive prosody, some practical suggestions for efficient prosody-centred DaF/DaZ instruction will be given. The teaching method aims at training prosodic competence in order to prevent or to eliminate the typical foreign accent of Italian learners of German, both beginners and advanced learners. Prosodic competence does not only enhance phonetic and prosodic performance, in most cases even native-like German phonetics and prosody, it also improves oral competence leading both to correct phonetic production and perception and to overall comprehension.